Panggilan Gereja Memperjuangkan Realitas Ketidakadilan Pendidikan Anak - Kristi Kristi; Aristia Heronia Agrecya Huwaa; Omega Ritawaemahu; Sofenda Putri Stevany Soulissa (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Education is a fundamental human right that must be guaranteed for every child without discrimination. In Indonesia, particularly in the Ambon region, educational inequality remains a serious challenge influenced by geographical, socio-economic, and structural factors. Children from impoverished families and remote areas often lack access to adequate education due to limited facilities, low-quality teaching staff, and inadequate technological infrastructure. This situation not only hinders children’s potential development but also perpetuates cycles of poverty and social injustice. Data from the Ministry of Education and Culture (2021) indicates low basic education participation rates and high dropout rates in Maluku and Ambon. In response, the church in Ambon, as highlighted by Joseph Lourine Since (2023), plays a strategic role through the Marginalized Children’s Development School (Sekolah Pembinaan Anak Marginal - SPAM), an alternative education program integrating academic learning with Christian character and spiritual formation. This initiative embodies the preferential option for the poor principle in liberation theology, as developed by Gustavo Gutiérrez, positioning the church as an advocate for the marginalized in its social and moral mission. This abstract recommends strengthening the church’s role in education through multisectoral collaboration to create a more just and inclusive education system for marginalized children.